The Indian connection of the Thailand moss flora, with one new species, Fissidens elizbrowniae - Narin Printarakul (2018)
© 2014 Royal Botanic Gardens and Domain Trust. Twenty species of mosses from northern Thailand are reported as new to the moss flora of the country. One of these, Fissidens elizbrowniae B.C.Tan & K.Wongkuna-Thananoppakun is described as a new species. Among the new records, a number of species exhibit a continuous range or disjunctive distribution between India and Thailand (Indochina), highlighting the little known floristic connection between the moss floras of Thailand (Indochina) and the Indian subcontinent. Other new moss records represent probable members of either the East Asiatic or Sino-Himalayan floras.